Endoscopic Decompression and Marsupialization of A Duodenal Duplication Cyst - Eliza I-Lin Sin; Ennaliza Salazar; Christopher Jen Lock Khor; Yee Low (Elsevier, 2018)
Introduction: Duodenal duplication cysts are rare congenital foregut anomalies, accounting for 2%-12% of all gastrointestinal tract duplications. Surgical excision entails risk of injury to the pancreaticobiliary structures due to proximity or communication with the cyst. We present a case of duodenal duplication cyst in a 3 year-old boy who successfully underwent endoscopic decompression. Case report: AT is a young boy who first presented at 15 months of age with abdominal pain. There was one subsequent episode of pancreatitis. Ultrasonography showed the typical double wall sign of a duplication cyst and magnetic resonance cholangio-pancreatography showed a large 5 cm cyst postero-medial to the second part of the duodenum, communicating with the pancreaticobiliary system and causing dilatation of the proximal duodenum. He subsequently underwent successful endoscopic ultrasound guided decompression at 3 years of age under general anesthesia, and had an uneventful postoperative recovery. Conclusion: Endoscopic ultrasound guided assessment and treatment of gastrointestinal duplication cysts is increasingly reported in adults. To the best of our knowledge, only one case of endoscopic treatment of duodenal duplication cyst, in an older child, has been reported thus far in the paediatric literature. In this paper, we review the current literature and discuss the therapeutic options of this rare condition.